Cutaneous B-cell lymphomas: pathogenesis, diagnostic workup, and therapy - Nicolay, Jan Peter; Wobser, Marion (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
Cutaneous B-cell lymphomas (CBCLs) comprise a group of mature lymphoproliferative B-cell disorders that primarily affect the skin. Characterized by great biological and clinical variability among its various subtypes, CBCLs fundamentally differ from primary nodal or systemic B-cell lymphomas. Given their uncomplicated course and excellent prognosis, lymphoma classifications rank primary cutaneous marginal zone lymphoma (PCMZL) and primary cutaneous follicle center lymphoma (PCFCL) as indolent CBCLs. By contrast, diffuse large B-cell lymphoma, leg type (DLBCL-LT) in particular, represent more aggressive lymphoma variants associated with a poorer prognosis. Therapeutic decisions and diagnostic procedures are based on the exact histological and immunohistochemical classification as well as the exclusion of systemic involvement and thus differentiation from nodal and systemic lymphomas. In this context, the diagnostic workup should also include molecular biology methods. Primary therapeutic options for indolent CBCL lesions include surgery and radiation therapy, as well as systemic treatment with rituximab (anti-CD20 antibody) in case of dissemination. More aggressive CBCLs usually require a combination of rituximab and polychemotherapy, primarily the CHOP regimen or modifications thereof. Given that the pathogenesis and biology of CBCLs has not been conclusively elucidated, and given the limited therapeutic armamentarium available, there is great need for comprehensive research, especially with respect to DLBCL-LT.
Gesehen am 28.03.2019